Programa Academia – Enseñanza Media Técnico Profesional (Emtp) – Vía Acceso Directo A La Educación Superior - Garrido Garrido, Gloria; Rosas Villalobos, Sandra; Bobadilla Ramírez, Gerardo (Congresos CLABES, 2024)
This document presents indisputable data of the Technical-Professional Education Academy Program (EMTP), obtained through permanent accompaniment, monitoring of class attendance, permanence in the Program and dropout, of students who opt for enrollment via direct access to higher education. Gradual follow-up to prevent dropouts, avoid dropouts and maintain the highest retention rate has been a primary objective for the Programme. The expectations of the students and the social impacts that are linked, clearly go hand in hand with insertion, from the point of view of contribution to society and in accordance with institutional policies in order to have a greater number of people trained with the requirements of a demanding quality (Castaño, O, Arce, J. & Ochoa, A (2019); Escobar, J. & Guido, A. (2019); Chacón, A. (2008); Escobar, J.,Largo, E., & Pérez, C.A. (2006); Montoya, X (2008), are determining factors in the trajectory of the students corresponding to the 2021, 2022 and 2023 cohorts. In the first year (2021) retention was 69%, in the year (2022) it increased to 72%, followed by an abandonment rate of 31% and 28% respectively. Compared to the 2023 cohort, it reached a 27.5% dropout rate before the first assessment. The scores obtained in the Higher Education Access Test (PAES) show an average of 567 points, which is not enough for a normal application with the universe of applicants. Reasons for bad time management habits, and an observed socialization that requires reinforcement and complexity of subjects, are the findings that become challenges for the improvements of the next editions of the program.